Benzothiophene or Benzofuran Bridges in Diaryl Ethenes: Two‐Step Access by Pd‐Catalyzed CH Activation and Theoretical/Experimental Studies on Their Photoreactivity. Issue 32 (7th July 2014) - Yuan, Kedong; Boixel, Julien; Chantzis, Agisilaos; Jacquemin , Denis; Guerchais, Véronique; Doucet, Henri
Abstract A series of terarylenes incorporating benzothiophene (BT)/benzofuran (BF) as the central ethene unit was synthesised by using sequential Pd‐catalysed CH activation reactions. This new methodology allows the easy modification of the nature of the pendant heteroarene groups. Diaryl ethene (DAE) derivatives with thiophene, thiazole, pyrrole, isoxazole and pyrazole rings were prepared. A large number of asymmetrical DAEs are easily accessible by this new method in both the BT and BF series. The study of their photochromic properties in solution revealed that the nature of the heteroarene and of the central unit drastically modify their photochromic behaviour. TD‐DFT calculations were performed to assess the nature of the relevant excited states.